Transnationalized Tourism: Hyper-Advantages from Global Competitiveness - USHAKOV, Denis; ROBU, Elena; BLAGORAZUMNAIA, Olga; KABAHA, Salam (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).02, 2020)
Due to synergy effects from transnationalization, corporation gets its own set of global competitive advantages which can be called using the prefix hyper- (which means, first of all, the global measure of these competitive advantages, that is, company’s capacity to make use of them at any regional or world market; secondly, massive opportunities which these advantages provide for company’s strategic and tactical activities; and thirdly, low probability that any small or mid-sized company would be able to get same or similar competitive advantages). Therefore, economic efficiency of any transnational corporation operating in the tourism sector can be viewed from the standpoint of 6H model. To these 6Hs belong: hyper-profit, hyper-competitiveness, hyper-presence, hyper-positioning, hyper-mobility and hyper-prospective. The article will consider all these hyper-advantages of TNCs along with the sources of their origin.